Toxic effect and inability of L-homoserine to be a nitrogen source for growth of Escherichia coli resolved by a combination of in vivo evolution engineering and omics analyses - Alkim, Ceren; Farias, Daniele; Fredonnet, Julie; Serrano-Bataille, Helene; Herviou, Pauline; Picot, Marc; Slama, Nawel; Dejean, Sebastien; Morin, Nicolas; Enjalbert, Brice; François, Jean M. (Frontiers in Microbiology, 2022)
L-homoserine is a pivotal intermediate in the carbon and nitrogen metabolism of E. coli. However, this non-canonical amino acid cannot be used as a nitrogen source for growth. Furthermore, growth of this bacterium in a synthetic media is potently inhibited by L-homoserine. To understand this dual effect, an adapted laboratory evolution (ALE) was applied, which allowed the isolation of a strain able to grow with L-homoserine as the nitrogen source and was, at the same time, desensitized to growth inhibition by this amino acid. Sequencing of this evolved strain identified only four genomic modifications, including a 49 bp truncation starting from the stop codon of thrL. This mutation resulted in a modified thrL locus carrying a thrL* allele encoding a polypeptide 9 amino acids longer than the thrL encoded leader peptide. Remarkably, the replacement of thrL with thrL* in the original strain MG1655 alleviated L-homoserine inhibition to the same extent as strain 4E, but did not allow growth with this amino acid as a nitrogen source. The loss of L-homoserine toxic effect could be explained by the rapid conversion of L-homoserine into threonine via the thrL*-dependent transcriptional activation of the threonine operon thrABC. On the other hand, the growth of E. coli on a mineral medium with L-homoserine required an activation of the threonine degradation pathway II and glycine cleavage system, resulting in the release of ammonium ions that were likely recaptured by NAD(P)-dependent glutamate dehydrogenase. To infer about the direct molecular targets of L-homoserine toxicity, a transcriptomic analysis of wild-type MG1655 in the presence of 10 mM L-homoserine was performed, which notably identified a potent repression of locomotion-motility-chemotaxis process and of branched-chain amino acids synthesis. Since the magnitude of these effects was lower in a thrL mutant, concomitant with a twofold lower sensitivity of this mutant to L-homoserine, it could be argued that growth inhibition by L-homoserine is due to the repression of these biological processes. In addition, L-homoserine induced a strong upregulation of genes in the sulfate reductive assimilation pathway, including those encoding its transport. How this non-canonical amino acid triggers these transcriptomic changes is discussed